Pengelolaan Surat Masuk dan Surat Keluar di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Yomi, Agustia Permata; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2015)
Based on analyzing the data, it was concluded the following things: first, the management of incoming mail at the Library and Archives of West Sumatra Province include: (1) receipt; (2) noted the activities of the script; (3) distribute to the activity; (4) processing letters; (5) store the control card. While the management of outgoing mail in the Library and Archives of West Sumatra Province include: (1) drafting; (2) approval of the concept; (3) typing letters; (4) the signing of a letter; (5) the recording of the letter; (6) the provision of official stamp; (7) cellophane; (8) delivery. Secondly, the obstacles encountered in the management of incoming and outgoing mail at the Library and Archives of West Sumatra Province include: (1) not all letters submitted to the clerk; (2) officers are often negligent because one of the numbering; (3) one employee returns the letter; (4) the lack of number of employees; (5) the handling of mail is often done by children field workers; (6) does not discipline employees; (7) employees home before work hours. Third, the efforts made to overcome te obstacles encountered in the management of incoming and outgoing mail at the Library and Archives of West Sumatra Province Include: (1) the head of the leadership should do the briefing; (2) the officer should be more careful in the management letter; (3) the officer must always exercise control over the employee; (4) the institution should use a computer system to keep the letter; (5) should be given sanction to employees who are not disciplined in his work. Keywords: management of incoming; management of outgoing